Thymidine Phosphorylase Regulates the Expression of CXCL10 in Rheumatoid Arthritis Fibroblast‐like Synoviocytes. Issue 3 (March 2014) - Toyoda, Yuko; Tabata, Sho; Kishi, Jun; Kuramoto, Takuya; Mitsuhashi, Atsushi; Saijo, Atsuro; Kawano, Hiroshi; Goto, Hisatsugu; Aono, Yoshinori; Hanibuchi, Masaki; Horikawa, Hideaki; Nakajima, Toshihiro; et al.
<x xml:space="preserve">Abstract</x> Objective Thymidine phosphorylase (TP) in rheumatoid arthritis (RA) fibroblast‐like synoviocytes (FLS) is induced by tumor necrosis factor α (TNFα) and other cytokines that have been reported to be major inflammation mediators in RA. We previously demonstrated that TP plays an important role in angiogenesis and tumor growth, invasion, and metastasis. The aim of this study was to investigate whether the role of TP in the pathogenesis of RA is similar to its role in tumors. Methods In FLS obtained from 2 patients with RA, the expression of TP, interferon‐γ (IFNγ)–inducible protein 10 (CXCL10), and other cytokines was measured by quantitative real‐time polymerase chain reaction, immunoblotting, and enzyme‐linked immunosorbent assays. Microarray analysis was performed using FLS transfected with TYMP complementary DNA and treated with a TP inhibitor. Results The expression of TP in FLS was up‐regulated by TNFα, interleukin‐1β (IL‐1β), IL‐17, IFNγ, and lipopolysaccharide. Microarray analysis of FLS overexpressing TP identified CXCL10 as a thymidine phosphorylase–related gene. The expression of CXCL10 was induced by TNFα, and this induction was suppressed by TYMP small interfering RNA and TP inhibitor. Furthermore, the combination of TNFα and IFNγ synergistically augmented the expression of TP and CXCL10. TP‐induced CXCL10 expression was suppressed by the antioxidant EUK‐8. In the synovial tissue of patients with RA, TP levels were significantly correlated with CXCL10 expression. Conclusion The combination of TNFα and IFNγ strongly induced the expression of thymidine phosphorylase in RA FLS. The induction of thymidine phosphorylase enhanced the expression of CXCL10, which may contribute to the Th1 phenotype and bone destruction observed in RA.